New Industrial Master Plan 2030: Prioritise Common Diseases — Ahmad Mahfuz Gazali - Ahmad Mahfuz, Gazali (Social Health Analytics Sdn Bhd, 2023)
It is imperative to encourage more companies to manufacture minimally invasive devices, point-of-care products, and medical devices to support the NIMP.